Основные понятия и положения социокультурного подхода и специфика их применения в социологии - Черныш, Н.; Ровенчак, О. (Социология: теория, методы, маркетинг, 2006)
The authors analyze three major sociological interpretations of socio- cultural approach as well as suggest their own conceptual model based on these approaches. The
model synthesizes the most fruitful ideas of the above mentioned interpretations and
examines the potential of sociological implementations. The underlying text considers
the main concepts and theses that constitute a theoretical frame of the model; it also
presents an approximate attempt of their operationalization.